2020
DOI: 10.1111/aos.14404
|View full text |Cite
|
Sign up to set email alerts
|

Microbial keratitis and clinical outcomes following penetrating and endothelial keratoplasty

Abstract: The goal of this study was to review the incidence, risk factors and outcomes of microbial keratitis after penetrating keratoplasty (PK) and endothelial keratoplasty (EK). Methods: The electronic medical records at Wills Eye Hospital were queried for cases of microbial keratitis following PK or EK performed between 1 May 2007 and 1 September 2018. Charts were reviewed to obtain demographic data, transplant characteristics, details of microbial keratitis, graft survival and clinical outcomes. Results: During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 30 publications
3
34
1
1
Order By: Relevance
“…ocular surface-related infection or IIK). A large retrospective cohort study of 2,098 keratoplasty performed between 2007 and 2018 in the US observed a PKIK incidence of 5.9% and 1.3% following PKP and EK, respectively ( 24 ). The higher proportion of PKIK occurring in PKP (93%) compared to DALK (6%) and EK (0%) was similarly depicted in a UK study of 1,508 grafts ( 25 ).…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…ocular surface-related infection or IIK). A large retrospective cohort study of 2,098 keratoplasty performed between 2007 and 2018 in the US observed a PKIK incidence of 5.9% and 1.3% following PKP and EK, respectively ( 24 ). The higher proportion of PKIK occurring in PKP (93%) compared to DALK (6%) and EK (0%) was similarly depicted in a UK study of 1,508 grafts ( 25 ).…”
Section: Epidemiologymentioning
confidence: 99%
“…The higher proportion of PKIK after PKP hinges on a combination of factors, including the indication for surgery, the use of sutures, and the prolonged use of topical corticosteroids. The indications for EK tend to be non-infective causes such as endothelial dystrophy, whereas a wider range of ocular comorbidities indicated for PKP may include IK and repeat (high-risk) grafts ( 24 ). Additionally, the requirement for corneal sutures in PKP, compared to EK, poses substantial risk of IK.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial keratitis is the most frequent type of infectious keratitis, mostly associated with the use of contact lenses (Delgado et al, 2008;Álvarez-Feĺix et al, 2010;Eltis, 2011;Bispo et al, 2015). Worldwide, the main etiologic agents of bacterial keratitis are Gram-positive cocci (Staphylococcus aureus, S. epidermidis, Streptococcus pneumoniae, S. pyogenes, S. viridans), followed by Gram-negative bacillus Pseudomonas aeruginosa (Álvarez-Feĺix et al, 2010;Hernańdez-Camarena et al, 2012;Hernandez-Camarena et al, 2015;Di Zazzo et al, 2020;Dohse et al, 2020;Singh et al, 2020). Eye fungal infections or keratomycosis in the cornea are commonly produced by corneal trauma.…”
Section: Introductionmentioning
confidence: 99%
“…and Aspergillus sp. are the most isolated filamentous fungi (Seal and Pleyer, 2007;Vanzzini-Zago et al, 2010;Hernańdez-Camarena et al, 2012;Di Zazzo et al, 2020;Dohse et al, 2020;Singh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%